2020
DOI: 10.2174/1871523018666190319144020
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Radiation-induced Pneumonitis and Lung Fibrosis using Alpha-lipoic Acid and Resveratrol

Abstract: Background: Lung is a radiosensitive organ. Studies have shown that exposure of the lung to acute and high doses of radiation following inhalation of radioactive agents or an accidental radiological event may lead to pneumonitis and fibrosis, which are associated with a risk of death. So far, some agents have been studied for mitigation of pneumonitis and fibrosis following exposure of murine lung tissues to ionizing radiation. In this study, we aimed to detect the possible mitigatory effect of alpha-lipoic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…This was supported by the nding conducted by Azmoonfar et.al. (Azmoonfar et al 2019) who reported that ALA was able to mitigate brosis and pneumonitis markers in mice lung tissues following lung irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by the nding conducted by Azmoonfar et.al. (Azmoonfar et al 2019) who reported that ALA was able to mitigate brosis and pneumonitis markers in mice lung tissues following lung irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…The microscope’s field of view was 22 for ocular lens and 5.512 for objective lens. Thereafter, results were reported and scored according to our previous study [17].…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies in the recent decade have tested the ALA-associated anti-inflammatory effects on rats [78][79][80][81][82][83][84][85][86] and mice [87,88]. The model disorders included multiple-organ sepsis [78,81,82,86], endotoxemia [79], metal or organic poisoning [81,84], and radiation-induced damage [88]. Altogether, ALA administration was found to decrease inflammatory response, H 2 O 2 , MDA levels, myeloperoxidase activity, and cytokine levels.…”
Section: Mitochondrial Nutrients: Action Mechanisms and Antioxidant Pmentioning
confidence: 99%
“…Of patients Duration Effects References ALA Hemodialysis 63 8 weeks Decreased C-reactive protein (CRP) [ 83 ] Cardiopulmonary surgery 30 24 ± 9.4 months Significantly decreased IL-6 and IL-8 levels [ 84 ] Ischemia–reperfusion injury 26 > 14 days Decreased inflammatory markers, and early kidney dysfunction and pancreatitis [ 85 ] CoQ10 Septic shock 14 72 h Significantly lower CoQ10 plasma levels in septic shock patients than in healthy controls. CoQ10 negatively associated with inflammatory molecules [ 86 ] Acute influenza 50 3 influenza seasons Significantly lower CoQ10 plasma levels in patients with acute influenza infection [ 87 ] Papillomavirus skin warts 156 90 days Decreased viral load and increased antiviral cytokine levels [ 88 ] CARN Hemodialysis or chronic peritoneal dialysis 113 6 months Suppressed inflammation, CRP [ 89 ] Hemodialysis 42 6 months Decreased CRP [ 90 ] Hemodialysis …”
Section: Introductionmentioning
confidence: 99%